Korelasi Antara Minat Membaca dengan Keterampilan Menulis Teks Fantasi pada Siswa Kelas VII SMP Negeri 1 Ngabang - Claranti, Fatnianti Selvia; Wiguna, M. Zikri; Yuda, Ramadhan Kusuma (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine whether there is a relationship between reading interest and the ability to write fantasy texts among seventh-grade students at SMP Negeri 1 Ngabang. This study uses a quantitative method with a correlational research type. The instruments used are questionnaires, tests, and documentation. The population of this study includes seventh-grade students, totaling 225 students, with a sample of 32 students selected from class VII H. Data analysis was conducted using the Product Moment correlation technique. The results showed that the calculated r was smaller than the table r (-0.066 < 0.349), so it can be concluded that there is no significant relationship between reading interest and the ability to write fantasy texts among the students studied